BOOKS RECENTLY PUBLISHED. (Notes, 2013)
A list of recently published books related to music is presented, including "Perfect Lives: An Opera," by Robert Ashley, "Scoring With Logic Pro," by Jay Asher and "Handel," 2nd ed. by Donald Burrows.